Peningkatan Hasil Belajar Peserta Didik Kelas X SMA Stella Duce 1 Yogyakarta pada Materi Suara Hati Melalui Model Pembelajaran Problem Based Learning - Ana Pawestrin; Anselmus Yata Mones; Maria Margaretha Dwilinda (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the learning outcomes of Catholic religious and ethics subjects education on the material of conscience through the learning model of Problem Based Learning. This class action research involves 36 students of class X-4 SMA Stella Duce 1 Yogyakarta in the 2023/2024 academic year. The action was carried out in two learning cycles. Data were collected with assessments in each cycle, and observation guidelines, and analyzed descriptively. The results of the class action research showed that in cycle I the average value of summative assessment results 1 of 36 students was 74.3 with a percentage of value categories of 11.1% feasible, 83.3% advanced and 5.6% proficient. And in cycle II the average value of summative assessment results 2 of 36 students was 91.2 with a percentage of value categories of 13.9% advanced and 86.1% proficient. Thus, applying the Problem-Based Learning model can improve students' learning outcomes.